2016
DOI: 10.1186/s13287-016-0440-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured scaffold as a determinant of stem cell fate

Abstract: The functionality of stem cells is tightly regulated by cues from the niche, comprising both intrinsic and extrinsic cell signals. Besides chemical and growth factors, biophysical signals are important components of extrinsic signals that dictate the stem cell properties. The materials used in the fabrication of scaffolds provide the chemical cues whereas the shape of the scaffolds provides the biophysical cues. The effect of the chemical composition of the scaffolds on stem cell fate is well researched. Bioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 121 publications
1
87
0
3
Order By: Relevance
“…In the last decade, many studies have shown the possibility of using stem cells associated with hydrogels or scaffolds in tissue engineering [28,29]. Outstanding interest was reserved to the hydrogels that were based on hyaluronic acid [30][31][32], a natural component of the extracellular matrix of connective tissues, that has several activities [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, many studies have shown the possibility of using stem cells associated with hydrogels or scaffolds in tissue engineering [28,29]. Outstanding interest was reserved to the hydrogels that were based on hyaluronic acid [30][31][32], a natural component of the extracellular matrix of connective tissues, that has several activities [33].…”
Section: Discussionmentioning
confidence: 99%
“…Micro‐ and nanotopological features are present in native ECM and can alter cell alignment and phenotype . Cells interact with the features of ECM via a host of cell‐surface receptors, including integrins, growth factor receptors, and cell surface heparan sulfate proteoglycans .…”
Section: Control Of Msc Differentiation Through Material‐based Mechanmentioning
confidence: 99%
“…Substrates with micro‐ and nanotopography seek to mimic the patterns found in native ECM and have shown promise as tools for altering cellular phenotype . Fabrication techniques can be used to create features including parallel grooves, posts, convex and concave microlenses, and pits, that vary in dimensions, stiffness, and material composition. The nanopatterns and substrate stiffness provide biophysical cues that may be similar to those provided by the native fibrillar structure of ECM components.…”
Section: Control Of Msc Differentiation Through Material‐based Mechanmentioning
confidence: 99%
“…The geometry of a substrate also determines the orientation and rate of cell growth . As we know, the three‐dimensional (3D) micromechanical environment of a cell in in vivo, the surfaces of the various developed scaffolds for cellular studies and tissue engineering, and the surfaces of the various developed microcarriers for cell culturing are normally not flat or are normally curved. Since the surface curvature of a substrate is a major descriptive parameter of the geometry of the substrate, studies on the cellular responses to the surface curvature of a substrate are necessary for understanding the cellular behaviors in 3D micromechanical environments and for designing effective and efficient 3D micromechanical environments to control cell and tissue developments.…”
Section: Introductionmentioning
confidence: 99%